2019
DOI: 10.1136/bmjopen-2019-030208
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of how services supporting women with perinatal mental health difficulties work with their families: a qualitative study in England

Abstract: ObjectivesPartners and wider family members play a vital role in relation to women’s perinatal mental health. Clinical guidelines in the UK and internationally recommend that services supporting women with perinatal mental health difficulties involve and support their families too. However, little is known about family members’ needs and experiences, or whether they feel included by mental health services. This study set out to explore this.MethodsThis research formed part of a wider study exploring experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…Previous research has shown that partners often feel overlooked in the perinatal period and that the healthcare professionals focus exclusively on the women and babies. 12 18 Our findings did not indicate that the partners felt marginalised in relation to the ObPostCons. However, future research may benefit from including more on partners’ perspective.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Previous research has shown that partners often feel overlooked in the perinatal period and that the healthcare professionals focus exclusively on the women and babies. 12 18 Our findings did not indicate that the partners felt marginalised in relation to the ObPostCons. However, future research may benefit from including more on partners’ perspective.…”
Section: Discussioncontrasting
confidence: 66%
“… 17 The partners also emphasised a need for information and dialogue but were often not met in their needs, and described a feeling of being marginalised because of a mother–baby focus. 12 18 Although there is no evidence of reducing psychological trauma, it seems like there is a need for a postnatal consultation following a traumatic childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐synthesis of 20 studies of the experiences of fathers reported that services tend to focus on individual women (and babies), with a marginalization and neglect of women's partners and an unmet need for information by these partners 168 . A recent qualitative study, based on separate interviews with women with mental illness and a participant‐nominated “significant other”, also emphasized the complexity of involving and supporting partners and families, particularly when relationships are poor 169 .…”
Section: Interventionsmentioning
confidence: 99%
“…In practice, many countries do not have practitioners trained specifically for the perinatal period. Qualitative studies suggest that receiving interventions within generic services can be experienced as unhelpful by women 189,195 , partly due to the therapists' failure to understand the potential impact of mental disorders on maternal functioning 195 , and poor facilities for infants 169,195 , though, as RCTs in LMICs demonstrate, task‐shifting is possible if staff are suitably trained 96 .…”
Section: Service Deliverymentioning
confidence: 99%
“…Therefore, alongside establishing a measure's accuracy, we need to understand the acceptability of both the measure and of the identification strategy more broadly, from the perspectives of parents and health professionals. There are known barriers to seeking and accepting help, both for new and expectant parents, and for men (47)(48)(49)(50)(51)(52). Other relevant considerations include the ability of services to both identify and respond to needs, and any possible impact of these assessments on women's care or the couple relationship.…”
Section: Introductionmentioning
confidence: 99%